A Ternary Catalytic System for the Room Temperature Suzuki-Miyaura Reaction in Water - Aires da Conceição Silva; Jaqueline Dias Senra; Andréa Luzia Ferreira de Souza; Luiz Fernando Brum Malta (The Scientific World Journal)
The formation of Pd(0) in the absence of any classical reducing agent in a medium containing Mg2+/Al3+ layered double hydroxide (LDH) and N,N-dimethylformamide was evidenced. XRD analysis showed the presence of crystalline phases of palladium in the Pd/LDH composite. Suzuki-Miyaura reactions in aqueous medium were carried out at room temperature, and good yields were obtained with bromoarenes and iodoarenes using the ternary system LDH-Pd-CD (cyclodextrin) as catalyst.